Fine Grinding Of Hematite In Planetary Mill And Its Application As Dye Decolorization Catalyst - Arbain, Roshaida (2012)

(untitled)
Fine grinding of hematite in planetary mill was carried out by varying the mill rotational speed and grinding time in both, dry and wet conditions. The ground samples were characterized in terms of the specific surface area, mechanochemical effect through X-ray diffraction and Infrared Spectroscopy and its morphology. Specific surface area of 40.2 m2/g was achieved through dry and wet grinding condition with energy consumed of 76.8 kWh/kg and 30.7 kWh/kg respectively. Ground hematite in wet condition at 600 rpm for 10 h and 400 rpm for 25 h exhibits complete phase transformation from hematite (α-Fe2O3) to magnetite (Fe3O4) whilst in dry condition, no phase changes was observed. The degree of crystallinity ranges from 5.76% to 49.81% and 4.39% to 56.1% in dry and wet conditions, respectively with variation in lattice parameters either expansion or shrinkage. The minimum crystallite size obtained was 17.1 nm which exhibits lattice strain of 0.846 in dry grinding condition at 600 rpm for 10 h. The mechanochemical effect is supported by changes of IR bands. The ground particle exhibits some level of aggregation in both grinding conditions. Finally, the selected ground samples were used as catalyst for decolourization of reactive dye, Remazol Red3B (RR3B) in batch mode. The smaller particle size of 75 nm decolourized at the rate of 95.8% within 10 min with minimum iron leached (<5 mgL-1) which fulfill the Environmental Quality (Industrial Effluent) Regulations 2009. The continuous mode for decolorization of RR3B was carried out and complete decolorization was achieved with low iron dissolution which demonstrates the possibilities of using ground hematite as catalyst for large-scale textile industry wastewater treatment applications.